Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) Dengan Model Human Organization Technology (HOT)-Fi - Dewi Uswatun Khasanah; Farid Wajdi; Hari Wujoso (LPPM STIKOM Tunas Bangsa, 2023)
Information system is a system consisting of interrelated components that interact to gather, process, store, and disseminate information required by an organization or individual to achieve specific goals. The information system also functions as a processor of daily transactions, supports managerial information, and organizational strategic activities, as well as external parties with necessary reports. HOT-Fit stands for Human, Organization, and Technology-Fit, which is an evaluation framework that combines concepts from the Information System Success Model (ISSM) with the IT-Organizational Fit Model. HOT-Fit is used to assess the compatibility between humans, organizations, and technology in information systems, particularly in healthcare information systems. The research type employed is analytical survey research or explanatory research with a cross-sectional design, where measurements and observations are conducted simultaneously at one point in time. This study utilizes a reflective measurement model assessed based on loading factors (correlations between component values and construct values) of indicators measuring the constructs. The success of implementing the Hospital Information System (SIMRS) is influenced by factors such as System Quality, System Use, and Net Benefit. Net Benefit is directly affected by system use, meaning that the higher the perceived benefits experienced by users in using SIMRS, the higher the users' intention to use SIMRS.